Relationship between rooting ability and some physiological characteristics about carbon and nitrogen nutrition in rice seedlings - REN Wan-jun; LU Ting-qi; ZHAO Zhong-cao; YANG Wen-yu (浙江大学学报. 农业与生命科学版)
The relationship between rooting ability and some physiological characteristics about carbon and nitrogen nutrition in rice seedlings was studied by field plot experiment. The result showed that, the significant positive correlation was found between the nitrogen contents of roots, leaf sheath, leaf blade and number of new roots. Nitrogen accumulation of plant was significant or highly significant positive correlated with root length of per plant, number of roots and root dry mass. The properties of rooting ability was variously negative correlated with soluble sugar contents of leaf blade, and it was positive correlated with soluble sugar content of leaf sheath. The amylase activity of roots was significant or highly positive correlated with root length of per plant, root mass and number of roots. There was positive significant correlation between amylase activity of leaf sheath and ATPase activity of rooting node and root, furthermore, the correlation coefficient between ATPase activity of root and ratio of root dry mass and whole-plant dry mass was 0.840 7 (P<0.01). The plant nitrogen content, soluble nitrogen content in leaf sheath, plant amylase and ATPase activity of seedlings raising on dry land bed was higher than that on wet land bed and on plastic tray, so it laid a good physiological foundation for stronger rooting ability.